Strategi Negosiasi dalam Menyelesaikan Konflik Antarbudaya di Lingkungan Perusahaan - Abidin Abidin; Alfia Eka Asmawatun; Nadiatul Umah (Jurnal Manajemen dan Budaya, 2026)
This study focuses on an in-depth analysis of the identification of factors causing intercultural conflict and the implementation and effectiveness of Negotiation Strategies as a primary tool in addressing Intercultural Conflict Management within companies. In an era of high global connectivity, multinational companies often face disputes arising from differences in cultural perspectives and values. The method applied in this analysis is a literature study, which involves collecting sources, reading, recording, and processing relevant information. Data were obtained from textbooks, journals, research articles, and literature reviews that summarize the topic studied. The findings of this study indicate that conflict can arise due to aspects of communication, differences in goals, leadership styles, task distribution, and team member welfare. Effective negotiation strategies involve developing relationships and trust, enhancing transparent communication, understanding root causes and cultural perspectives, and applying a collaborative approach in finding mutually beneficial solutions. The implementation of strategies such as Collaboration, Compromise, Accommodation, Mediation, and the Mutual Interest Approach has proven important for maintaining harmony, stability, and supporting the competitive performance of organizations. This study concludes that collaborative and integrative negotiation strategies, supported by an understanding of organizational culture, are key to transforming conflict friction into growth opportunities.